2019
DOI: 10.1128/mbio.00555-19
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Staphylococcus aureus Protein A to von Willebrand Factor Is Regulated by Mechanical Force

Abstract: Binding ofStaphylococcus aureusto the large plasma glycoprotein von Willebrand factor (vWF) is controlled by hydrodynamic flow conditions. Currently, we know little about the molecular details of this shear-stress-dependent interaction. Using single-molecule atomic force microscopy, we demonstrate that vWF binds to theS. aureussurface protein A (SpA) via a previously undescribed force-sensitive mechanism. We identify an extremely strong SpA-vWF interaction, capable of withstanding forces of ∼2 nN, both in labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
(57 reference statements)
1
32
1
Order By: Relevance
“…For example, high-affinity non-covalent interactions including Ni:His-tag and Biotin:Avidin have both been used as immobilization tags onto surfaces or as the object of study in AFM-SMFS (Fritz et al, 1998;Berquand et al, 2005;Dupres et al, 2005;Li et al, 2019), as shown in Figure 1B. Many different classes of receptor-ligands have been probed by AFM (Milles et al, 2017;Liu et al, 2019), including antibody-antigen interactions (Dammer et al, 1996;Hinterdorfer et al, 1996Hinterdorfer et al, , 1998Allen et al, 1997;Ros et al, 1998;Schwesinger et al, 2000;Kienberger et al, 2005;Sulchek et al, 2005Sulchek et al, , 2006Neuert et al, 2006;Odorico et al, 2007;Morfill et al, 2008;Roy et al, 2010;Bizzarri and Cannistraro, 2014;Klamecka et al, 2015;Tsai et al, 2016;Liu et al, 2019Liu et al, , 2020, avidin systems (see below), bacterial adhesion systems (Herman et al, 2014;Schoeler et al, 2014;Jobst et al, 2015;Nash et al, 2016;Alonso-Caballero et al, 2018;Herman-Bausier et al, 2018;Milles et al, 2018;Viela et al, 2019), and others (Sletmoen et al, 2004;Farrance et al, 2013).…”
Section: Measurement Configurations For Afm-smfsmentioning
confidence: 99%
“…For example, high-affinity non-covalent interactions including Ni:His-tag and Biotin:Avidin have both been used as immobilization tags onto surfaces or as the object of study in AFM-SMFS (Fritz et al, 1998;Berquand et al, 2005;Dupres et al, 2005;Li et al, 2019), as shown in Figure 1B. Many different classes of receptor-ligands have been probed by AFM (Milles et al, 2017;Liu et al, 2019), including antibody-antigen interactions (Dammer et al, 1996;Hinterdorfer et al, 1996Hinterdorfer et al, , 1998Allen et al, 1997;Ros et al, 1998;Schwesinger et al, 2000;Kienberger et al, 2005;Sulchek et al, 2005Sulchek et al, , 2006Neuert et al, 2006;Odorico et al, 2007;Morfill et al, 2008;Roy et al, 2010;Bizzarri and Cannistraro, 2014;Klamecka et al, 2015;Tsai et al, 2016;Liu et al, 2019Liu et al, , 2020, avidin systems (see below), bacterial adhesion systems (Herman et al, 2014;Schoeler et al, 2014;Jobst et al, 2015;Nash et al, 2016;Alonso-Caballero et al, 2018;Herman-Bausier et al, 2018;Milles et al, 2018;Viela et al, 2019), and others (Sletmoen et al, 2004;Farrance et al, 2013).…”
Section: Measurement Configurations For Afm-smfsmentioning
confidence: 99%
“…Such "catch" bonds ( 62) are proposed to exhibit longer lifetimes than their antonymous "slip" bonds, which is very useful to pathogens that need to stay adhered to their host-target tissues under hydrodynamic forces (58). AFM has provided evidence for the existence of catch bonds in ClfA, ClfB, and SpA (63)(64)(65), revealing that their binding strength is considerably increased by mechanical tension. The proposed mechanism involves force-induced conformational changes in the adhesins, from a weakly binding state to a strongly binding state, and explains how staphylococci can resist physical stresses such as hydrodynamic shear forces.…”
Section: Cell Adhesion Forcesmentioning
confidence: 99%
“…Another pertinent question is whether microbes express their adhesins homogenously or whether these form nanodomains capable of enhancing adhesion. FD-based imaging detected such clustering in S. aureus for various adhesins, including FnBPs, SdrG, ClfA, ClfB, SpA, and SpsL (48,64,69,70). It has been suggested that protein clustering on the cell surface may favor adhesion through multivalency.…”
Section: Cell Adhesion Forcesmentioning
confidence: 99%
“…These results led to the conclusion that ClfA interacts with Fg via two distinct binding sites, whose adhesive function is regulated by mechanical tension. Lastly, mechanical tension also activated the adhesive function of SpA (Viela, Prystopiuk, et al, ). Under tensile loading, the adhesin binds to the large plasma glycoprotein von Willebrand factor with a force of ~2,000 pN.…”
Section: Mechanical Stress Strengthens Microbial Cell Adhesionmentioning
confidence: 99%